Pengaruh Aset Pajak Tangguhan Dan Beban Pajak Tangguhan Terhadap Manajemen Laba Dengan Finanacial Distress Sebagai Variabel Moderasi Pada Perusahaan Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Tahun 2018 – 2021 - Khori Afifah Eka Putri; Mulyadi Mulyadi; Panata Bangar Hasioan Sianipar (Akuntansi, 2023)
Financial hardship as a moderator of the impact of deferred tax assets and deferred tax costs on profit management in food and beverage firms listed on the Indonesia Stock Exchange between 2018 and 2021. The purpose of this research is to find out how (1) deferred tax assets affect profit management, (2) deferred tax expenses affect profit management, (3) the impact of deferred tax assets on the relationship between profit management and financial distress, and (4) the impact of deferred tax expenses on that same relationship. For the years 2018-2020, the sample consists of food and beverage firms trading on the Indonesia Stock Exchange. This research uses a sample of 16 firms in the food and beverage industry that are listed on the Indonesia Stock Exchange between 2018 and 2021. According to the findings: (1) deferred tax assets positively affect profit management; (2) deferred tax expense positively affects profit management; (3) financial distress bolsters the effect of deferred tax assets on profit management; and (4) financial distress dampens the effect of deferred tax burden on profit management.